Understanding the Role of Co-Parenting Quality in Mediating the Effect of Parenting Stress on Child Adjustment - Conti, Marco; Romano, Giulia (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to investigate whether co-parenting quality mediates the relationship between parenting stress and child adjustment among parents in Italy. A descriptive correlational design was employed using a sample of 491 parents from Italy, selected based on the Morgan and Krejcie sample size table. Participants completed three standardized instruments: the Parenting Stress Index–Short Form (PSI-SF), the Co-Parenting Relationship Scale (CRS), and the Strengths and Difficulties Questionnaire (SDQ). Data were analyzed using SPSS-27 for descriptive statistics and Pearson correlation, and AMOS-21 for Structural Equation Modeling (SEM) to assess the mediating role of co-parenting quality in the relationship between parenting stress and child adjustment. The results showed that parenting stress was significantly negatively correlated with co-parenting quality (r = –.48, p < .001) and positively correlated with child adjustment difficulties (r = .52, p < .001). Co-parenting quality also showed a significant negative correlation with child adjustment problems (r = –.43, p < .001). SEM analysis confirmed a good model fit (χ² = 163.29, df = 84, χ²/df = 1.94, CFI = .97, RMSEA = .044, TLI = .96) and revealed that co-parenting quality partially mediated the effect of parenting stress on child adjustment. The total effect of parenting stress on child adjustment was β = .23 (p < .001), with a direct effect of β = .36 (p < .001) and an indirect effect via co-parenting quality of β = –.13 (p < .001). The findings underscore the importance of co-parenting quality as a protective relational factor that can buffer the adverse impact of parenting stress on children’s psychological adjustment. Enhancing co-parenting practices may be a key target in interventions aimed at promoting child well-being in stressed family systems.